Effectiveness of Auditory Visual Games Method on Students' Learning Interest in the Christian Religious Education Subject in Grade VIII - Ribka Wahyu Christiani; Telhalia Telhalia; Fernando Dorothius Pongoh (CV. Edujavare Publishing, 2026)
Education plays a fundamental role in developing students’ intellectual, moral, spiritual, and social competencies. This study aimed to determine the effectiveness and effectiveness level of the auditory-visual game method in increasing students' learning interest in Christian Religious Education among Grade VIII.8 students at SMP Negeri 8 Palangka Raya. The study employed a quantitative approach using a one-group pretest-posttest experimental design involving 15 Christian students selected through purposive sampling. Data were collected using a 20-item Likert-scale questionnaire measuring four indicators of learning interest: feelings of enjoyment, attraction, attention, and participation. The collected data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the paired sample t-test, and the N-Gain Score with the assistance of SPSS software. The findings revealed that the application of the auditory-visual game method significantly increased students' learning interest, as evidenced by a paired sample t-test significance value (Sig. 2-tailed) of less than 0.05, resulting in the rejection of the null hypothesis and acceptance of the alternative hypothesis. The mean learning-interest score increased from 48.53 in the pretest to 60.67 in the posttest. Furthermore, the average N-Gain Score of 0.399 (39.9%) indicated that the effectiveness level of the intervention was categorized as moderate. These findings demonstrate that integrating games with auditory and visual media creates a more engaging, interactive, and student-centered learning environment, thereby improving students' enjoyment, attraction, attention, and active participation in Christian Religious Education learning.